2021
DOI: 10.1002/hep.31651
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Four Pillars of Enterohepatic Bile Salt Cycling; Lessons From Genetics and Pharmacology

Abstract: Bile salts play a pivotal role in lipid homeostasis, are sensed by specialized receptors, and have been implicated in various disorders affecting the gut or liver. They may play a role either as culprit or as potential panacea. Four very efficient transporters mediate most of the hepatic and intestinal bile salt uptake and efflux, and are each essential for the efficient enterohepatic circulation of bile salts. Starting from the intestinal lumen, conjugated bile salts cross the otherwise impermeable lipid bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…Bile acids can be reabsorbed in the small intestine in a variety of ways. The distal ileum is the main site for bile acid reabsorption because the apical sodium-dependent bile acid transporter (ASBT) is mainly expressed here ( 53 ). Out et al found that ASBT-dependent ileal bile acid reabsorption was inhibited in intestinal Gata4 specific knockout mice, which is related to changes in gut microbiota in an ASBT-dependent pathway through Gata4 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids can be reabsorbed in the small intestine in a variety of ways. The distal ileum is the main site for bile acid reabsorption because the apical sodium-dependent bile acid transporter (ASBT) is mainly expressed here ( 53 ). Out et al found that ASBT-dependent ileal bile acid reabsorption was inhibited in intestinal Gata4 specific knockout mice, which is related to changes in gut microbiota in an ASBT-dependent pathway through Gata4 ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Uptake and efflux of BAs are mediated by a series of efficient BA transporters in the liver. Sodium taurocholate cotransporting polypeptide ( Ntcp ) and organic anion-transporting polypeptides ( Oatps ) are responsible for transporting BAs from portal blood into hepatocytes ( Kunst et al, 2020 ). mRNA expression of Oatp1a1 and Oatp1a4 was decreased significantly and increased in mice fed the LD, respectively, whereas APS reversed these changes ( Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…For sinusoidal uptake transporters, increased mRNA expression of Mrp3 and Mrp4 in the LD group was decreased significantly by APS supplementation ( Supplementary Figure S3A ). Bsep and Mrp2 pump bile salts out of hepatocytes into primary bile ( Kunst et al, 2020 ). mRNA expression of Bsep was increased significantly in mice fed the LD, but APS had little effect on mRNA expression of Bsep and Mrp2 ( Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile acids then travel via the portal vein back to the liver, where they are taken up from the sinusoids into the hepatocytes via SLC10A1 (or basolateral sodium taurocholate cotransporting polypeptide (NTCP)) transporter [ 4 , 5 ], thereby completing the enterohepatic circulation [ 6 ]. Importantly, the polarized distribution of apical and basolateral bile acid transporters in the hepatocytes and enterocytes thus is necessary for the enterohepatic circulation of bile acids [ 7 ] ( Figure 1 ).…”
Section: An Introduction To the Enterohepatic Circulation Of Bile mentioning
confidence: 99%